Cultural Importance and Use of Medicinal Plants in the Shipibo-Conibo Native Community of Vencedor (Loreto) Peru - Tudela-Talavera, Pío; La Torre-Cuadros, Maria de los Angeles; Community of Vencedor, Native (Ethnobotany Research and Applications, 2016)
The main objectives of this research were to determine which medicinal plants are culturally most important for the native community of Vencedor as well as testing a new measure of the cultural importance of medicinal plants that can be used outside of this one particular case. Data were collected through participant observation, informal conversation, and semi-structured and structured interviews to 31 heads of family. According to the Cultural Significance for Conservation Index (CSCI) developed, significant species were Petiveria alliacea L., Jatropha gossypifolia L., Mansoa alliacea (Lam.) A.H.Gentry, Hura crepitans L., and Banisteriopsis caapi (Spruce ex Griseb.) C.V.Morton. Our index showed a significant correlation with the other indices considered in this paper. We conclude that CSCI is a good indicator of the cultural importance of medicinal plants and that it can be useful in cases where there is a need to recognize which culturally important plants are more vulnerable.